GERAKAN SENDAWAR MAKMUR DI KABUPATEN KUTAI BARAT: HIDUP DAN BEREKONOMI TANPA PEMERINTAH - Edy Suandi Hamid; Endang Sih Prapti; Hudiyanto Hudiyanto; Mubyarto Mubyarto; Puthut Indroyono (Journal of Indonesian Economy and Business (JIEB), 2003)
The development of ekonomi rakyat in an isolated kampung, kecamatan, or kabupaten is becoming very important in the era of regional autonomy. One of this kabupaten is West Kutai in the Province of East Kalimantan. The size of the kabupaten is 31,629 km2 (as large as the size of Central Java Province) but the population is only 144.000 people (while Central Java’s is 35 million people) with the population density of only 4.5/km2. It is clear that it needs “more” population to exploit the rich natural resources. The 48% poverty is alarming to all concerned and the Bupati is doing everything possible to reduce poverty “as soon as possible” by introducing a mass movement called “Gerakan Sendawar Makmur” (Prosperous Sendawar Movement).Keywords: autonomy, participation, poverty alleviation, cultural economics.